THE DEVELOPMENT OF LAPAROSCOPIC SURGERY AT THE N.V. SKLIFOSOVSKY RESEARCH INSTITUTE FOR EMERGENCY MEDICINE - M. Sh. Khubutiya; A. S. Yermolov; P. A. Yartsev; A. A. Gulyayev; V. T. Samsonov; V. D. Levitsky; D. T. Tkeshelashvili (Неотложная медицинская помощь)
Today, in connection with the development of surgical techniques, one of the main tasks is minimization of surgical trauma, reduction of postoperative complications and mortality, as well as the timing of hospital treatment of patients with maintained quality of surgical care. The widespread adoption of endoscopic surgery techniques into daily practice may help achieve the goal.Annually, we perform more than 450 laparoscopic surgeries for acute surgical diseases at the Institute, and we have performed more than 6,000 interventions since 2000. however, the laparoscopic method of surgery is not a priority, there are strict indications and contraindications, which we followed and thus avoided the development of iatrogenic complications associated with the use of this method for urgent diseases. Today, the laparoscopic technique is used in acute appendicitis, perforated gastric ulcer and duodenal ulcer, acute cholecystitis, strangulated hernia of the anterior abdominal wall, intestinal obstruction, as well as in patients with abdominal trauma. The use of the laparoscopic method in emergency abdominal surgery improves the quality of diagnosis and treatment, reduces the number of postoperative complications and mortality, as well as the time of treatment.